HUBUNGAN ANTARA PERSEPSI TERHADAP KOMPETENSI DOSEN MATA KULIAH PSIKOLOGI PERKEMBANGAN DENGAN MOTIVASI BELAJAR MATA KULIAH PSIKOLOGI PERKEMBANGAN PADA MAHASISWA DI UNIVERSITAS NEGERI JAKARTA - Muzdalifah, Fellianti (Intuisi : Jurnal Psikologi Ilmiah, 2009)
This survey investigated correlation between the perception of lecturer’s competency of developmental psychology subject and students’ learning motivation who attended in developmental psychology class in State University of Jakarta. This study involved 58 students as a sample. Both, data on perception lecture's competency and learning motivation of developmental psychology subject were obtained through the use Likert alike questionaires. The overall process of data used SPSS v.12.00. The results indicates that there was a positive significant relationship between perception of lecturer’s competency of developmental psychology subject with learning motivation of students who attended in developmental psychology class in State University of Jakarta. It’s meant that when students perceived lecturer’s competency higher it will be followed by their learning motivation